Antifungal Activity Test of Jamaican Cherry Leaf (Muntingia calabura l.) Ethanol Extract in Inhibiting Growth of Fungi Malassezia furfur and Pityrosporum ovale - Khairani, Tetty Noverita; Neswita, Elfia; Nurasni, Nurasni; Fitri, Khairani; Amanda, Asri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The plant species known as Jamaican Cherry Leaf (Muntingia calabura L.) belongs to the Muntingiaceae family. Flavonoid compounds, tannins, saponins, and steroids are all found in Jamaican cherry leaves. One of them has antifungals that can stop Pityrosporum ovale and Malassezia furfur from growing, and it is utilized as a traditional medication. This study aimed to determine the antifungal activity and the most effective concentration of Jamaican cherry leaves in inhibiting the growth of Malassezia furfur and Pityrosporum ovale fungi. Methods research is an experimental research. The research phase includes sampling, making simplicia, extract making, testing the characteristics of simplicia and extract, testing the inhibitory power of ethanol extract of Jamaican cherry leaf against fungi (Malassezia furfur and Pityrosporum ovale) by comparing the 2% ketoconazole antibiotic. The results showed the inhibition of ethanol extract of Jamaican cherry leaf (Muntingia calabura L.) against the growth of Malassezia furfur at F1 (7.2 mm), F2 (9.8 mm), F3 (11 mm) with and F4 (6.8 mm). mm) while against the growth of the fungus Pityrosporum ovale at F1 (7.0 mm), F2 (9.11 mm), F3 (10.2 mm) and F4 (6.3 mm). The best inhibition zone was formed at 30% concentration treatment with strong category. The conclusion shows that the ethanol extract of Jamaican cherry leaf (Muntingia calabura L.) can inhibit the growth of Malassezia furfur and Pityrosporum ovale fungi.